Design and simulation of reduced switch converter based solar PV and energy storage fed shunt active power filter with butterfly optimization - Koganti Srilakshmi; Sravanthy Gaddameedhi; Alapati Ramadevi; Praveen Kumar Balachandran; J. Ganesh Prasad Reddy; Ramprasad Vangalapudi (Results in Control and Optimization)
This work optimally designs the shunt active power filter powered by battery storage and a solar PV system in addition to the reduced switch converters connected across DC bus. The gain values of the proportional integral controller for the shunt and energy storage system are considered as control parameters and properly adjusted utilizing a nature-inspired butterfly optimization algorithm. This proposed work seeks to accomplish the following main goals: (1) stabilizing DC bus voltage within a short period of time (sec) during load and sun irradiation variations (2) suppressing harmonics in current waveforms thereby improving power factor. The efficiency of the optimally designed controller is examined with three test studies using MATLAB/Simulink. Subsequently, the obtained outcomes are then compared with the standard fuzzy logic, PIC, sliding mode controllers in addition to genetic algorithm, biogeography-based optimization metaheruristic methods. Upon analyzing the results, it is evident that the suggested approach gives a Total Harmonic Distortion of 2.27 %, 2.24 %, and 4.555 % for the three test cases respectively. However, this THD values are lower when compared to other methods, in addition DC bus voltage is achieved within a short settling time of 0.02 s.